A Study on Human Resource Management and Practical Strategies in Japanese Enterprises in China Based on Cultural Differences - Zhang, Yichen (Transactions on Economics, Business and Management Research, 2024)
The complexity of human resource management (HRM) in multi-business multinational companies is evident, especially when operating across different geographical regions, which is particularly pronounced in the context of Japanese companies operating in China. In this environment, cultural conflicts and barriers are prevalent, presenting unique challenges for HRM. Despite similarities in certain cultural aspects between China and Japan, significant differences in language, non-verbal behavior, customs, modes of thought, and values have a profound impact on HRM strategies. This study focuses on the HRM strategies of Japanese companies in China and their solutions. By conducting a thorough examination of HRM methods in the context of Japanese companies operating in China, this study aims to reveal the challenges of managing cultural differences and related practices. It discusses how to manage and integrate cultural differences in a cross-cultural and multi-business environment, emphasizing the crucial role of cultural integration in achieving management goals. This study analyzes how Japanese-owned enterprises in China address cultural differences and provides management practice strategies aimed at bridging these differences and committed to providing practical strategies for managers to address and bridge cultural differences and achieve the company's globalization goals.